Serotonin and the rat adrenal gland - Shaikh, Soraya (University of Edinburgh, 1987)
Serotonin (5HT) is an indoleamine with potent in vitro and in vivo effects on aldosterone biosynthesis in the adrenal zona glomerulosa of several species including Man and the rat. Its physiological role in the control of aldosterone secretion however, is not well understood. The purpose of these studies was to clarify its possible role in aldosterone biosynthesis using the rat as an experimental model. Attempts to localise 5HT within the adrenal gland using a specific monoclonal antibody to 5HT with the avidin-biotin detection technique, suggested, that serotonergic nerves are not present in the adrenal cortex although appreciable levels of 5HT were measured by HPLC in adrenal tissue ( 1.7 ± 0.2 μg/ g wet weight). The storage and metabolism of 5HT in isolated zona glomerulosa cells and inner cortical and, medullary cells was investigated using [³ H]-5HT as a marker. Zona glomerulosa cells rapidly metabolised 5HT, whereas the inner zones were able to store or retain 5HT to a greater extent. Stimulation of steroidogenesis by 5HT however, was confined to the zona glomerulosa cells of the adrenal cortex. The interaction of 5HT with specific 5HT receptors was investigated by studying the effects of the 5HT antagonists, methysergide and ketanserin on the steroidogenic response to 5HT in isolated zona glomerulosa cell suspensions. Methysergide (10-⁶M) inhibited the corticosterone and aldosterone responses to 5HT (10-⁹M - 10-⁶)and angiotensin II (10-⁹M, 10-⁸M). In addition, it significantly inhibited the corticosterone response to ACTH. Ketanserin (10-⁶M) also inhibited the corticosterone and aldosterone responses to 5HT (10-⁹M, 10-⁹M) and All (10-⁹M, 10-⁹M) but did not affect ACTH-stimulated steroidogenesis. Neither antagonist affected the steroidogenic responses to potassium. A change in dietary salt intake of rats did not lead to any significant change in either the blood levels or adrenal contents of 5HT. The in vitro- responsiveness of adrenal cells to 5HT however, was altered by changing the sodium status. An overall view of changing endogenous levels of 5HT in vivo in the rat was explored using the 5HT-depleting agent, PCPA and the immediate 5HT-precursor, 5-hydroxytryptophan (5HTP). Treatment with PCPA led to a decrease in blood 5HT levels and a loss of in vitro responsiveness to 5HT and All in subsequent preparations of zona glomerulosa cells. Treatment with 5HTP produced higher blood levels of 5HT and an enhanced responsiveness of subsequent preparations of zona glomerulosa cells. These studies suggest that 5HT from central and/or peripheral sources such as platelets or mast cells, could exert a tonic effect on aldosterone secretion from the rat adrenal zona glomerulosa, which is mediated by the activation of specific receptors for 5HT.
Keywords: Biochemistry; Human; anatomy